PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 24 PEKANBARU - Nuryati Nuryati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2015)
This research is motivated by the fact that is found in the class V Elementary School 24 Pekanbaru, which shows the results of learning science is still relatively low. Formulation the problem in this research is: